The Using Of Biofilter and Aquatic Plants to Remediated Organic Pollutants in Liquid Waste Originated From Rubber Factory, as Fish Live Media - Dedi Fernandes Saragih; M Hasbi; Budijono ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The waste water originated from rubber factory contain high concentrationof organic matter. Direct disposal of these waste to waters may negative impactsto aquatic organisms. To reduce the risk, the waste should be treatment. Theseresearch conducted from Desember 2013 – February 2014. The study aims tounderstand the effectiveness of biofilter and aquatic plants reactors to reduceorganic pollutants in the waste water originated from the rubber factory and thenused these water as fish life media. The water quality measured were BOD5 andCOD, beside it measured survival rate of fishes in the aquarium. Sampling forwater quality and fish were conducted 3 times, once/ two weeks. The resultsshown effectiveness BOD5 range 82,6% – 87,8% and COD range 80,8% – 84,4%.But in the control (without biofilter and aquatic plants shown low effectiveness ofBOD5 and COD were 50,1 – 55,1% and 38,2 – 44,5% respectively. Survival rateof Pangasius hypopthalmus (80%), Oreochromis niloticus (76,67%), andCyprinus carpio (70%) and in the control, survival rate of Pangasiushypopthalmus (56,67%), Oreochromis niloticus (36,67%), and Cyprinus carpio(23,33%). Based on data obtained, it can be concluded that the biofilter andaquatic plant was effective to reduce BOD and COD content in the rubber factorywaste water.Keywords: Rubber waste water, Biofilter, Aquatic plants